2005
DOI: 10.1586/14737167.5.4.479
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of discrete-choice methods to economic evaluations of complementary and alternative medicine

Abstract: This review discusses the potential contributions of discrete-choice methods of stated preference assessment to future economic evaluations of complementary and alternative medicine. The manner in which some complementary and alternative medicine practitioners and researchers have framed the concept of therapeutic benefits including process-related benefits is first discussed. The mechanics of a discrete-choice exercise including assessment of health state utilities and willingness to pay are then described. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…6 In addition, some commentators have further suggested that the current application of economic evaluation techniques may be limited in CM given the inability of these techniques to accurately capture both the absolute magnitude of process-related benefits from CM and their magnitude relative to conventional treatment. 9,10 While CBA is considered to be the ''gold standard'' in economic evaluation, 8 the application of this technique in evaluating health care interventions is somewhat limited. This is due to the ethical issues surrounding the valuation of health improvement and ultimately human life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 In addition, some commentators have further suggested that the current application of economic evaluation techniques may be limited in CM given the inability of these techniques to accurately capture both the absolute magnitude of process-related benefits from CM and their magnitude relative to conventional treatment. 9,10 While CBA is considered to be the ''gold standard'' in economic evaluation, 8 the application of this technique in evaluating health care interventions is somewhat limited. This is due to the ethical issues surrounding the valuation of health improvement and ultimately human life.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the ethical issues surrounding the valuation of health improvement and ultimately human life. 10,11 However, a recent advance in the economics literature is the development of tools to translate underlying preferences and outcomes (both process and final) into monetary terms. The most common measure of benefit in monetary terms is willingness to pay (WTP) 12 and there are two commonly accepted techniques to estimate WTP: contingent valuation methods (CV) and discrete choice experiments (DCE).…”
Section: Introductionmentioning
confidence: 99%